Literature Review : Peran Keluarga dalam Keberhasilan Pengobatan Tuberkulosis - Syahrizal Syahrizal; Hendra Kurniawan; Nadhira Alfina Harahap; Reza Kurniawan (Yayasan Literasi Sains Indonesia, 2026)
Tuberculosis (TB) remains a major public health problem in Indonesia, with persistent challenges related to treatment adherence and completion due to the long duration of therapy. Non-adherence to TB treatment contributes to treatment failure, drug resistance, and continued transmission. Family involvement plays a crucial role in supporting TB patients throughout the prolonged treatment period and is considered an important component of patient-centered TB care. This study aimed to review the role of family support in the success of tuberculosis treatment through a structured literature review. A systematic literature search was conducted following PRISMA guidelines using Google Scholar, PubMed, and Garuda databases for articles published between 2015 and 2025. Eligible studies were analyzed using a narrative and thematic synthesis approach. The findings indicate that family support significantly contributes to improved treatment adherence, prevention of treatment default, reduction of stigma, and better overall treatment outcomes. Family roles identified include emotional support, instrumental assistance, provision of health information, and supervision of medication intake as treatment observers. However, several barriers were identified, including limited family knowledge about TB, persistent social stigma, and economic burden during treatment. Strengthening family-centered care through education, empowerment, and social support is essential to improve TB treatment success and achieve national TB control targets.